KEEFEKTIFAN MULTIMEDIA PEMBELAJARAN INTERAKTIF MATERI SISTEM TATA SURYA UNTUK MENINGKATKAN PEMAHAMAN KONSEP IPA DAN KEMANDIRIAN BELAJAR SISWA SD - Sultan; Wasino; Sarwi; Tri Joko Raharjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop interactive multimedia learning materials on the solar system to improve elementary school students' understanding of science concepts and independent learning. The research was motivated by the suboptimal use of technology-based learning facilities due to teachers' limited abilities, resulting in conventional, teacher-centered learning that has an impact on students' low conceptual understanding and learning independence. The research method used was the ADDIE Research and Development (R&D) model, which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects consisted of sixth-grade elementary school teachers and students divided into experimental and control classes. Data were collected through concept comprehension tests and self-assessment scales of learning independence using pre-tests and post-tests, then analyzed using N-Gain, independent t-tests, paired t-tests, and MANOVA. The results showed that the N-Gain value for concept understanding in the experimental class was 0.5523 and for learning independence was 0.451, both of which were in the moderate category and higher than the control class, which was in the low category. The independent t-test results show a significant post-test difference between the experimental and control classes in concept comprehension and learning independence. The paired t-test results show a significant increase from the pre-test to the post-test in the experimental class in science concept comprehension and learning independence compared to the control class. The MANOVA test results show that interactive learning multimedia has a significant simultaneous effect on students' understanding of science concepts and learning independence (Sig. = 0.000). Thus, interactive learning multimedia on the solar system material is proven to be effective in improving elementary school students' understanding of concepts and learning independence.